"Turn-off" photoelectrochemical aptasensor based on g-C3N4/WC/WO3 composites for tobramycin detection. (1st March 2023) - Qiao, Lu; Zhu, Yuan; Zeng, Tianjing; Zhang, Yuanyuan; Zhang, Mingjuan; Song, Kexin; Yin, Nian; Tao, Yani; Zhao, Yue; Zhang, Yi; Zhang, Chang
Highlights: High photoelectrochemical (PEC) g-C3 N4 /WC/WO3 were prepared by simple one-pot calcination method. TOB aptamer probes were immobilized on the surface of g-C3 N4 /WC/WO3 via π–π stacking interaction. The proposed PEC aptasensor possessed a low detection limit of 2 pg mL −1 . Abstract: Tobramycin (TOB), as a widely used antibiotic, poses severe unpredictable risks to ecology and health. Here, a novel photoelectrochemical (PEC) aptasensor based on a "turn-off" PEC mode was constructed for TOB detection. The working electrode could be modified by g-C3 N4 /WC/WO3 composites and TOB aptamer probes in turn. The TOB aptamer probes could anchor on the g-C3 N4 /WC/WO3 through π-π stacking interaction to avoid interference from other modifications. When TOB was captured by the aptamer probes anchored on the modified fluorine-doped tin oxide (FTO) electrode, a decreased photocurrent was obtained owing to steric hindrance and hinder electron transfer. Under optimal conditions, 0.005–5 ng mL −1 of TOB could be detected with a detection limit as low as 2 pg mL −1 . Meanwhile, actual samples were investigated as well. The proposed sensor shows high specificity, satisfactory detectability, great reproducibility, and may provide a new thought for detecting other pollutants.